NANOSCIENCE AND TECHNOLOGY: THE NEXT REVOLUTION IN THE EARTH SCIENCES - Hochella M.F. (My University, 2002)
Nanoscience and technology are not exactly new, but nevertheless rapidly expanding fields that are providing revolutions in all sciences on the scale of what genomics and proteomics have done in recent years for the biological sciences. Nanoscience is based on the fact that properties of materials change as a function of the physical dimension of that material, and nanotechnology takes advantage of this by applying selected property modifications of this nature to some beneficial endeavor. The prefix 'nano' is used because the property dependence on physical size is generally observed close to the nanoscale, somewhere around 10-9 m. The dimensions at which changes are observed depend on the specific material and the property in question, as well as which of the three dimensions are restricted in real space (e.g. small particles vs. thin films vs. 'one-dimensional' phases). Properties change in these confined spaces because the electronic structure (i.e. the distribution of electron energies) of the material is modified here in the gray area between the bulk and atomistic/molecular realms, or equivalently between the continuum and strictly quantum domains. Earth materials with at least one dimension in the nanorange are essentially ubiquitous. Many have been known for several decades and more are being discovered all the time. But the scientific emphasis has now shifted to that of measuring, understanding and ultimately predicting the property changes from the bulk to nanodomains, and to the understanding of the significant ways that Earth processes are affected by these changes. In addition, where possible, Earth scientists are using nanoscience to develop nanotechnology that should play important roles in Earth sustainability issues of the future.
Keywords: NANOSCIENCE; NANOTECHNOLOGY; SOLUBILITY; PARTICLES; CRYSTALS; SCANNING TUNNELING MICROSCOPY; ATOMIC FORCE MICROSCOPY